Principle of Ecological Restorative Justice in Corporate Environmental Crimes Policies - Absori, Absori; Arief Budiono; Maya Khater; Chetan Mukundan; Restu Mufanti (Contrarius, 2026)
Environmental crimes pose a significant threat to ecological integrity and public welfare. However, law enforcement utilising retributive justice often fails to address the root causes of environmental damage caused by corporations. Therefore, alternative law enforcement efforts are necessary for more effective outcomes. This research aims to determine the effectiveness of current law enforcement against corporate environmental crimes in Indonesia, examine environmental crime enforcement in other countries, and identify an integrative environmental law enforcement policy model that incorporates the restorative justice approach in handling corporate environmental crimes. This study employs a normative legal research method with three approaches: statutory, conceptual, and comparative. This study finds that, first, law enforcement against corporate environmental crimes in Indonesia remains ineffective due to the difficulties in proving corporate liability, weak coordination and capacity among law enforcement agencies, and low levels of corporate compliance and transparency. Second, compared to Indonesia, Australia, specifically Victoria, has established a more comprehensive restorative justice framework through the Environment Protection Act 2017, whereas New South Wales still relies on judicial practice without an explicit restorative legal basis. Third, Indonesia needs to adopt an ecological restorative justice model that places environmental restoration, community participation, independent oversight, and stringent sanctions at the core of corporate criminal liability to truly realise ecological justice. Therefore, it is necessary to formulate law enforcement policies that incorporate ecological restorative justice principles, prioritising environmental restoration. Corporations should face sanctions and be required to restore damage in a tangible, measurable way, with independent oversight.